Phenotypic characterization of inflammatory cells from osteoarthritic synovium and synovial fluids - Haynes, Mark K (Clinical immunology (Orlando, Fla.), 2002)
Osteoarthritis (OA) is considered a degenerative joint disorder caused by mechanical wear to the articular surface. However, while joint injury, obesity, and mutations in collagen increase the risk of developing OA, evidence implicates inflammatory mechanisms in disease progression and chronicity. To address this question we used FACS analysis, immunohistochemistry, and in vitro cell culture to evaluate inflammatory mechanisms in synovial fluids and joint tissues obtained after arthrocentesis or knee replacement surgery. Immunohistochemistry revealed a significant T cell infiltrate in six of nine tissue specimens. T cells were present throughout the synovial membrane and were particularly localized around vasculature and in large cellular aggregates. Cells within the aggregates expressed markers associated with immune activation and antigen presentation. T cells from OA synovial fluids expressed an activated phenotype and synthesized interferon-gamma following in vitro stimulation. These data support the hypothesis that inflammatory cells play a significant role in OA disease progression and chronicity